Optimization of Traffic Accident Investigations by the Gakkum Unit to Realize Fair Law Enforcement at the Sukoharjo Police - Lastiqa, Hanafi Allief (Advances in Police Science Research Journal, 2024)
This final project has a background of the many unresolved traffic accident cases in the last five years. Therefore, it is necessary to take steps to solve the problem as an optimization of traffic accident investigations by the Unit of Legal Action for Traffic Unit of the Sukoharjo Police. The research project aims to: (1) Describe the traffic accident investigation management system by the traffic unit of the Sukoharjo Police and (2) describe the organization resources of the Law Enforcement Unit in the traffic accident investigations. This essay used conceptual theory and concept literature as a problem analysis tool. The concepts and theories used are: POAC theory or management theory, elements of 6M management theory, SWOT Theory, Optimization Concept, Traffic Accident Investigation Concept, and Law Enforcement Concept. This final project used a qualitative approach method, this type of research Field Research, primary and secondary data sources. Data collection techniques were carried out by means of interviews, observations, and document studies. At the stage of data validity, the authors used data triangulation techniques consisting of source triangulation, technical triangulation, and time triangulation. The research was conducted in Sukoharjo Regency, from the research results, the writer found several obstacles that hindered the traffic accident investigation process. These obstacles include, among others, that there are still many personnel who do not pay attention to SOPs in carrying out their duties, such as giving APP by the leadership which is not implemented. The personnel do not know the daily activity plan because of the lack of distribution by the leadership, the implementation of case titles which are rarely carried out, the number of personnel who are less when compared to the situation and conditions of Sukoharjo Regency, and there are still investigators who do not have accident investigator certification. In terms of facilities and infrastructure, there are also obstacles such as the insufficient number of investigator vehicles and the absence of ambulances and cranes. The condition of the community is also an obstacle because there are still many people who do not report traffic accidents immediately. Suggestions from the author are that the Head of Traffic pays more attention to routine activities carried out by personnel and the quality of personnel and must pay more attention to unresolved traffic accident cases to become an evaluation of future traffic accident investigations.